IPR 103 - Rustic dwarf arabic coffee cultivar more adapted to hot regions and poor soils - Sera,Tumoru (2013)
'IPR 103' was derived from a cross between "Catuaí" and "Icatu". 'IPR 103' is a medium size dwarf cultivar with high rusticity, partially resistant to coffee leaf rust with late ripening. This cultivar is more adapted to hot regions and poor soils. It presents partial resistance to necrosis and mummification of young fruits on field conditions.